(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article explores the psychological foundations of an integrative pedagogical model and modern recruiting strategies in ensuring educational effectiveness within higher education institutions. In the context of rapid socio-economic transformation and digitalization, universities are increasingly required to align educational processes with labor market demands. An integrative pedagogical model combines cognitive, motivational, socio-emotional, and competency-based dimensions of learning, while modern recruiting strategies emphasize psychological assessment, adaptability, and professional identity alignment. The study synthesizes contemporary psychological theories, including self-determination theory, social-cognitive theory, constructivism, and competency-based education frameworks, to analyze how integrative pedagogy and recruitment mechanisms interact in shaping student outcomes. Empirical data collected from university students and early-career professionals demonstrate that educational environments incorporating integrative pedagogical principles significantly enhance professional readiness, self-efficacy, and career adaptability. Furthermore, recruitment systems grounded in psychological diagnostics improve alignment between individual potential and organizational needs. The findings highlight the importance of bridging educational psychology and human resource psychology to ensure sustainable educational effectiveness.